2023
DOI: 10.1002/lno.12392
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of an Antarctic cryptophyte to increasing temperature, CO2, and irradiance

Abstract: The Southern Ocean, a globally important CO2 sink, is one of the most susceptible regions in the world to climate change. Phytoplankton of the coastal shelf waters around the Western Antarctic Peninsula have been experiencing rapid warming over the past decades and current ongoing climatic changes will expose them to ocean acidification and high light intensities due to increasing stratification. We conducted a multiple‐stressor experiment to evaluate the response of the still poorly studied key Antarctic cryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…However, in the presence of high CO 2 (a condition associated with ocean acidification), this light sensitivity phenotype was alleviated. Growth of G. cryophila was also stimulated under warming temperatures (Camoying and Trimborn, 2023). The conditions of higher and variable light combined with warmer temperatures and high CO 2 match climate-driven changes in the WAP.…”
Section: Cryptophytesmentioning
confidence: 79%
See 1 more Smart Citation
“…However, in the presence of high CO 2 (a condition associated with ocean acidification), this light sensitivity phenotype was alleviated. Growth of G. cryophila was also stimulated under warming temperatures (Camoying and Trimborn, 2023). The conditions of higher and variable light combined with warmer temperatures and high CO 2 match climate-driven changes in the WAP.…”
Section: Cryptophytesmentioning
confidence: 79%
“…Cryptomonad isolates from the MDV lakes are currently unavailable and so detailed knowledge of their physiology and response to varying environmental conditions is limited. A closely related isolate Geminigera cryophila, has been studied for several years and has yielded significant information regarding its ability to acclimate to a number of environmental variables (Trimborn et al, 2019;Camoying and Trimborn, 2023). These studies have revealed that the marine cryptophyte exhibits physiological plasticity to respond to variations in temperature and light.…”
Section: Cryptophytesmentioning
confidence: 99%